Deletion of D-Lactate Dehydrogenase A in Neisseria meningitidis Promotes Biofilm Formation Through Increased Autolysis and Extracellular DNA Release - Sigurlásdóttir, Sara; Wassing, Gabriela M.; Zuo, Fanglei; Arts, Melanie; Jonsson, Ann-Beth (Frontiers in Microbiology, 2019)
Neisseria meningitidis is a Gram-negative bacterium that asymptomatically colonizes the human nasopharyngeal mucosa. Pilus-mediated initial adherence of N. meningitidis to the epithelial mucosa is followed by the formation of three-dimensional aggregates, called microcolonies. Dispersal from microcolonies contributes to the transmission of N. meningitidis across the epithelial mucosa. We have recently discovered that environmental concentrations of host cell-derived lactate influences N. meningitidis microcolony dispersal. Here, we examined the ability of N. meningitidis mutants deficient in lactate metabolism to form biofilms. A lactate dehydrogenease A (ldhA) mutant had an increased level of biofilm formation. Deletion of ldhA increased the N. meningitidis cell surface hydrophobicity and aggregation. In this study, we used FAM20, which belongs to clonal complex ST-11 that forms biofilms independently of extracellular DNA (eDNA). However, treatment with DNase I abolished the increased biofilm formation and aggregation of the ldhA-deficient mutant, suggesting a critical role for eDNA. Compared to wild-type, the ldhA-deficient mutant exhibited an increased autolytic rate, with significant increases in the eDNA concentrations in the culture supernatants and in biofilms. Within the ldhA mutant biofilm, the transcription levels of the capsule, pilus, and bacterial lysis genes were downregulated, while norB, which is associated with anaerobic respiration, was upregulated. These findings suggest that the absence of ldhA in N. meningitidis promotes biofilm formation and aggregation through autolysis-mediated DNA release.